MOLECULAR CHARACTERIAZATION OF CHINESE IMPORTED FISH (ICEFISH) - A. Armani; L. Castigliego; A. Guidi; L. Tinacci; D. Gianfaldoni (Italian Journal of Food Safety, 2011)
Neosalanx spp and Protosalanx spp are two genuses belonging to the fish family of Salangidae that are caught in China and commercialised abroad with the name of Ice fish or silver fish. Because of their morphological resemblance to some valuable fish products sold on our national market (know as Bianchetto and Rossetto), the Icefish is sometimes involved in commercial frauds. The number of species of the aforesaid genuses are several and sometimes difficult to identify. However, the deep exploitation of the Salangids in China brought to a sharp prevalence of the specie Neosalanx taihuensis on the others, which should be the main if not the only specie imported in Italy. In this work, we analysed the DNA sequences of the cytochrome b of a number of Icefish samples collected both in Italy and in China, to evaluate the species which are actually imported, in order to develop, in the future, a single step molecular analysis for the identification of substitution frauds."